A Bluetooth Based Spoken Query System for Controlling Electronic Devices - Sarma, Hirakjyoti; Deka, Manoj (International Journal of Computer Sciences and Engineering, 2025)
This paper discusses a spoken query system developed for accessing some household electronic devices. The developed system enables the user to access these devices remotely by calling the system using a GSM modem/ Mobile phone. The spoken query system has mainly two modules i.e. interactive voice response (IVR) and automatic speech recognition (ASR) modules, which can be developed using open source resources. In the development of ASR models, the system specific data are collected from people of different ages and genders. The issues of data preparation, Training and Testing are performed by using HTK as a speech recognition tool. The system can recognize sample data i.e. the voice commands independent of vocabulary size, noise, and speaker characteristics. The recognized voice command as a text file will be used as an input into the microcontroller that is responsible to control the electronic home appliances. This speaker independent interactive voice response system is based on HMM (Hidden Markov Model) which is found to give a relative improvement of accuracy by more than 50%.